Analytical performances of the AMPLIQUICK® Respiratory Triplex assay for simultaneous detection and differentiation of SARS-CoV-2, influenza A/B and respiratory syncytial viruses in respiratory specimens. - Ralph-Sydney Mboumba Bouassa; Serge Tonen-Wolyec; David Veyer; Hélène Péré; Laurent Bélec (PLoS ONE)
Although patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza A, influenza B and respiratory syncytial virus (RSV) show comparable or very similar manifestations, the therapeutic approaches of these respiratory viral infections are different, which requires an accurate diagnosis. Recently, the novel multiplex real-time reverse transcription-polymerase chain reaction assay AMPLIQUICK® Respiratory Triplex (BioSynex SA, Illkirch-Graffenstaden, France) allows simultaneous detection and differentiation of SARS-CoV-2, influenza A, influenza B, and RSV in respiratory tract samples. We herein evaluated the performance of the AMPLIQUICK® Respiratory Triplex for the detection of the four viruses in respiratory specimens, using Allplex™ Respiratory Panel 1 and 2019-nCoV assays (Seegene, Seoul, Korea) as reference comparator assays. A total of 359 archived predetermined respiratory samples, including 83, 145, 19 and 95 positive specimens for SARS-CoV-2, influenza A, influenza B and RSV respectively, were included. The AMPLIQUICK® Respiratory Triplex showed high concordance with the reference assays, with an overall agreement for SARS-CoV-2, influenza A, influenza B, and RSV at 97.6%, 98.8%, 98.3% and 100.0%, respectively, and high κ values ranging from 0.93 to 1.00, indicating an almost perfect agreement between assays. Furthermore, high correlations of cycle threshold (Ct) values were observed for positive samples of the four viruses between the AMPLIQUICK® Respiratory Triplex and comparator assays, with an overall high agreement between Ct values assessed by Bland-Altman analyses. In conclusion, these observations demonstrate that the multiplex AMPLIQUICK® Respiratory Triplex is a reliable assay for the qualitative detection and differentiation of SARS-CoV-2, influenza A, influenza B, and RSV in respiratory specimens, which may prove useful for streamlining diagnostics during the winter influenza-seasons.